2016
DOI: 10.1515/rrlm-2016-0041
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects on the HMG-CoA Reductase in the chemical constituents of the Cassia mimosoides Linn

Abstract: Cassia mimosoides Linn has been used from ancient times and used for treating hepatitis for its supposedly medically beneficial properties. In this study, different constituents of the Cassia mimosoides Linn (β-Sitosterol, Oleanolic Acid, Emodin, Carotene, Resorcinol, Luteolin, and α-L-Rhamnose)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…Our sequential chromatographic experiments on the active fractions led to the isolation of 10 compounds, one of which was a mixture (Figure 1). Our structure elucidation studies indicated that five of them were abietane-type diterpenes (6,7-dehydroyleanone (1) [23], ferruginol (3) [24], horminone-7-acetoxyhorminone mixture (1:1) (6) (which were previously isolated from several Salvia species), 7-acetoxyhorminone (7) [25][26][27], and pisiferal (8) [28]); two nor abietane-type diterpenes (12-demethylmulticaulin (2) [29,30], and 12-hydroxy abieta-1, 3, 5 (10) 8, 11, 13-hexaene (4) [30,31]); one steroid (β-sitosterol (5) [32]); and two triterpenes (ursolic acid (9) [32] and oleanolic acid (10) [32]). Their structures were revealed using a combination of spectroscopic methods, e.g., UV, IR, 1 H-and 13 C-NMR-APT, HMQC, HMBC, and mass spectrometry (MS).…”
Section: Structure Elucidationmentioning
confidence: 89%
See 4 more Smart Citations
“…Our sequential chromatographic experiments on the active fractions led to the isolation of 10 compounds, one of which was a mixture (Figure 1). Our structure elucidation studies indicated that five of them were abietane-type diterpenes (6,7-dehydroyleanone (1) [23], ferruginol (3) [24], horminone-7-acetoxyhorminone mixture (1:1) (6) (which were previously isolated from several Salvia species), 7-acetoxyhorminone (7) [25][26][27], and pisiferal (8) [28]); two nor abietane-type diterpenes (12-demethylmulticaulin (2) [29,30], and 12-hydroxy abieta-1, 3, 5 (10) 8, 11, 13-hexaene (4) [30,31]); one steroid (β-sitosterol (5) [32]); and two triterpenes (ursolic acid (9) [32] and oleanolic acid (10) [32]). Their structures were revealed using a combination of spectroscopic methods, e.g., UV, IR, 1 H-and 13 C-NMR-APT, HMQC, HMBC, and mass spectrometry (MS).…”
Section: Structure Elucidationmentioning
confidence: 89%
“…β-Sitosterol, as a white powder (8 mg) (5), and a mixture of horminone and 7-acetoxyhorminone (1:1) (15 mg, orange crystal) (6), were isolated from the M-6 fraction (petroleum ether-dichloromethane: 1/2 solvent system) with the help of preparative thin layer chromatography (TLC). 7-Acetoxyhorminone (7) was isolated from the M-7 fraction as an orange crystal (10 mg) using a Sephadex column, followed by preparative TLC (petroleum ether-dichloromethane: 1/3). Pisiferal (8) was isolated from the M-8…”
Section: Isolation Of the Compoundsmentioning
confidence: 99%
See 3 more Smart Citations